2022
DOI: 10.21834/ebpj.v7i22.4145
|View full text |Cite
|
Sign up to set email alerts
|

Using the PAH in Teaching Reading to Sustain the Quality of EFL Students' Life

Abstract: Sustaining the quality of student life in any learning environment should be the priority of all educators. This situation becomes even more challenging when international EFL postgraduate students are expected to function in a learning environment where English is the medium of instruction. This study aimed to enhance their reading skills by implementing a learner-centred instructional framework referred to as the PAH (Pedagogy-Andragogy-Heutagogy) Continuum. This reading programme witnessed a significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Kaya (2015) also revealed that not being exposed to training in reading skills leads to Turkish EFL students' poor reading performance in exams. A similar situation has also been recorded for Chinese EFL students, and their dismal performance has been noted by researchers such as Du, Shamida et al (2022) and Hu, Sidhu et al (2022).…”
Section: Efl Students' Current Reading Performancesupporting
confidence: 76%
See 1 more Smart Citation
“…Kaya (2015) also revealed that not being exposed to training in reading skills leads to Turkish EFL students' poor reading performance in exams. A similar situation has also been recorded for Chinese EFL students, and their dismal performance has been noted by researchers such as Du, Shamida et al (2022) and Hu, Sidhu et al (2022).…”
Section: Efl Students' Current Reading Performancesupporting
confidence: 76%
“…Though China has integrated the teaching and learning of EFL for the past few decades, there is grave concern among authorities as a large majority of tertiary students leave universities with rather limited English language proficiency (Hu, Sidhu et al 2022). Therefore, several researchers, such as Du, Shamida et al (2022), have investigated the reasons behind this poor performance, and findings have revealed that Chinese EFL learners possess rather limited reading skills.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of a quality learning environment on student achievement has been articulated by several researchers, and it is a predominant factor in student well-being and success (Dhanapala, 2021;Du et al, 2022). Though there have been a plethora of studies examining the learning environment of tertiary students, there is scant empirical evidence focusing on the burgeoning field of postgraduate education.…”
Section: Introductionmentioning
confidence: 99%